2019
DOI: 10.1177/2051570719829432
|View full text |Cite
|
Sign up to set email alerts
|

Anthropomorphic virtual assistants and the reactions of Internet users: An experiment on the assistant’s voice

Abstract: Virtual assistants are increasingly common on commercial websites. In view of the benefits they offer to businesses for improving navigation and interaction with the consumers, researchers and practitioners agree on the value of providing them with anthropomorphic characteristics. This study focuses on the effect of the voice of the virtual assistant. Although there are some studies of human-computer interaction in this field, there is no work that addresses the topic from a marketing perspective and compares … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(49 citation statements)
references
References 89 publications
(163 reference statements)
1
44
0
1
Order By: Relevance
“…Eyssel et al [51] found that the effect was increased when the gender of the agent and participant matched. Chérif and Lemoine [25] found that human voices elicited greater social presence compared to synthetic voices in a website, but there was no effect on perceived trustworthiness. Chiou et al [27] found that the human voice was the most trusted and engaging, and human as well as high-quality synthetic voices were most credible.…”
Section: Anthropomorphism Humanlikeness and Natural Vs Synthetic Voicesmentioning
confidence: 98%
“…Eyssel et al [51] found that the effect was increased when the gender of the agent and participant matched. Chérif and Lemoine [25] found that human voices elicited greater social presence compared to synthetic voices in a website, but there was no effect on perceived trustworthiness. Chiou et al [27] found that the human voice was the most trusted and engaging, and human as well as high-quality synthetic voices were most credible.…”
Section: Anthropomorphism Humanlikeness and Natural Vs Synthetic Voicesmentioning
confidence: 98%
“…The strategic role of the human-like brand voice in developing the brand anthropomorphic profile is indirectly supported by Chérif and Lemoine (2019), who have shown that consumers who interact with a VA with a human voice (vs a synthetic voice) have a stronger perception of the VA as a human interlocutor.…”
Section: Human-like Brand Voicementioning
confidence: 99%
“…As VAs use natural language, interacts with users in real‐time and are characterized by human‐like attributes (such as voice), it is possible to expect that interactions with them may elicit a sense of social presence (Chattaraman et al, 2019; Chérif & Lemoine, 2019). Social presence is defined as the degree of salience of other person during an interaction (Short et al, 1976), while automated social presence is the “extent to which technology makes customers feel the presence of another social entity” (van Doorn et al, 2017, p. 1).…”
Section: Conceptual Developmentmentioning
confidence: 99%